Immigrant earnings profiles in the presence of human capital investment: Measuring cohort and macro effects - David A. Green; Christopher Worswick (Institute for Fiscal Studies (IFS), 2004)
Considering immigrant earnings in the context of post-arrival human capital investment implies: cohort quality should be defined in terms of the present value of the whole earnings profile; and, an appropriate definition of macro effects is obtained using the earnings profile of the native born cohort entering the labour market at the same time as an immigrant cohort. We illustrate this using Canadian immigrant earnings, where there were large cross-cohort earnings declines in the 1980s and 1990s. We find that changes affecting all new entrants play an important role in understanding immigrant earnings. In contrast, earlier approaches imply that macro events explain little of immigrant earnings patterns.
Keywords: J61; J31; 330